A Natural Antimicrobial Agent: Analysis of Antibacterial Effect and Mechanism of Compound Phenolic Acid on Escherichia coli Based on Tandem Mass Tag Proteomics - Zhang, Geyin; Yang, Yunqiao; Memon, Fareed Uddin; Hao, Kaiyuan; Xu, Baichang; Wang, Shuaiyang; Wang, Ying; Wu, Enyun; Chen, Xiaogang; Xiong, Wenguang; Si, Hongbin (Frontiers in Microbiology, 2021)
The purpose of this subject is to obtain a natural antibacterial agent. The five phenolic acids were combined with each other to obtain 31 combination drugs. Based on TMT proteomics, the antibacterial mechanism of the compound phenolic acid with the best antibacterial effect on multi-drug resistant Escherichia coli was comprehensively analyzed. The results showed that the compound phenolic acid 19, which was mixed in equal volume of protocatechuic acid, hydrocinnamic acid and chlorogenic acid, had the best antibacterial effect on Escherichia coli. At this time, the concentrations of protocatechuic acid, hydrocinnamic acid and chlorogenic acid were 0.833 mg/mL, 0.208 mg/mL, and 1.677 mg/mL, respectively. The treatment of compound phenolic acid 19 significantly down-regulated the proteins associated with the resistance (Tsr, Tar, CheA and CheW), OmpF and FliC of multidrug-resistant Escherichia coli. At the same time, we proved that compound phenolic acid 19 improves the sensitivity Escherichia coli to antibiotics (Ceftriaxone Sodium, Amoxicillin, Fosfomycin, Sulfamonomethoxine, Gatifloxacin, Lincomycin, Florfenicol, Cefotaxime Sodium and Rifampicin), causes the flagellum to fall off, breaks the structure of cell wall and cell membrane, and leads to macromolecules leaks from the cell. These evidences contribute to the development of new antibacterial drugs.